Surgical Technique of Fronto-orbital Advancement And Strip Craniectomy for Correction of Oxycephaly With Towering of Bregma, a Case Report (Bangladesh Journal of Neurosurgery, 2022)
Background: Craniosynostosis is a congenital problem of brain development that causes disfigurement of the head and face. Multiple synostoses is an abnormal development of head where fusion ofmany or all cranial sutures ’! oxycephaly (tower skull with undeveloped sinuses and shallow orbits). The most accepted surgical correction involves frontoorbital advancement and forehead remodeling.Aim of the Study: In this study, we described our experience and technique in surgical correction of multiple synostoses (Oxycephaly) in BSMMU,department of neurosurgery.Bang. J Neurosurgery 2022; 11(2): 134-137